A Study of Psychophysical Factor for Driver Fatigue Using Mathematical Model / Mohammad Firdaus Ani...[et al.] - Ani, Mohammad Firdaus; Kamat, Seri Rahayu; Husin, Kalthom (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The purpose behind the study is to develop the mathematical modeling of a psychophysical factors for drivers' fatigue, which can predict the relationship between the process input parameters and output response. Ten subjects participated in this study. The electromyography (EMG) responses were taken and evaluated using an Electromyography (EMG) device. The psychophysical factor such as muscle fatigue is one of the contributors to the drivers' fatigue problem, which led to road accidents among Malaysian. To efficiently formulate and develop the mathematical modeling of a psychophysical factors, the process modeling using Response Surface Methodology (RSM) was proposed. Design Expert 8.0.6 software was used in the RSM analysis. The mathematical model was successfully developed and validated. The modeling validation runs were within the 90% prediction interval of the developed model, and the residual errors compared to the predicted values were less than 10%. The significant parameters that influenced the muscle fatigue were also identified. Muscle fatigue was influenced by the time exposure, type of road, gender, interaction between time exposure and type of road, and interaction between type of road and gender. Throughout this study, the authors believe there is a new contribution to the body of knowledge.